Comparison of solvents for extraction of krill oil from krill meal: Lipid yield, phospholipids content, fatty acids composition and minor components - Xie, Dan; Jin, Jun; Sun, Jiang; Liang, Li; Wang, Xiaosan; Zhang, Wei; Wang, Xingguo; Jin, Qingzhe (Food chemistry, 2017)
•Comprehensive assessment of minor components in the extracted krill oil.•Comparison of seven different solvents for krill oil extraction from krill meal.•Subcritical butane proved to be an alternative to n-hexane and isohexane.•Extraction with acetone achieved high levels of minor components.•Ethanol and isopropanol resulted in high levels of PUFA and high PL contents. The effects of seven different extraction solvents (ethanol, isopropanol, acetone, ethyl acetate, isohexane, n-hexane, and subcritical butane) on the lipid yield and quality of the oil extracted from krill meal were investigated in this study. Phospholipids (PL), fatty acids (FA) composition and minor components including sterols, astaxanthin, vitamin A and tocopherols in the extracted krill oil were analyzed. The results indicated that ethanol and isopropanol led to comparatively higher lipid yields (16.33 and 14.52%, respectively) and PL contents (39.2 and 38.7%, respectively) but lower contents of the minor components than the other solvents. The krill oil extracted with acetone had the lowest PL content (20.63%) but contained more astaxanthin (206.74mg/kg), vitamin A (27.84mg/100g), and sterols (39.00mg/g). Moreover, high levels of n-3 FA were present in the extracts with high PL contents. Further analysis revealed that 23.65–28.10% of eicosapentaenoic acid (EPA) and 16.71–21.03% of docosahexaenoic acid (DHA) were present in the PL, while only 2.83–3.48% of EPA and 1.40–1.74% of DHA were detected in the triacylglycerols (TAG). In addition, subcritical butane proved to be an alternative to n-hexane and isohexane; krill oil extracted with these three solvents had similar qualities.